The Technology integration into English teaching at a vocational school in Indonesia: Benefits and challenges to introducing the Global English Paradigm - Utami, Rindya Santi; Samsudin, Asep (Politeknik Negeri Jember, 2026)
This qualitative study explores how Indonesian vocational school teachers integrate digital technology into English language teaching (ELT) and whether such practices align with the Global Englishes (GE) paradigm. Framed by Global Englishes theory, language ideology, and Technology-Enhanced Language Learning, the research addresses two core questions: (1) How is technology currently integrated into English teaching in vocational schools? and (2) What are the benefits and challenges faced by teachers in using technology to support the GE paradigm? .Data from interviews with four teachers in Jember, East Java, reveal that while tools like YouTube, WhatsApp, and Canva are widely used, their application tends to reinforce traditional norms rather than expose students to diverse English varieties. Challenges include exam-focused curricula, limited training, and native-speaker biases. The study proposes the Techno-Pedagogical Global Englishes (TPGE) framework to analyze how technology can both support and constrain GE-based pedagogy. Findings highlight the need for reflective teacher training and curricular reform to promote more inclusive, real-world English learning.